From Horse to Electricity: An Environmental and Technological Outlook in the Transformation of the Tram System in Chile Towards the End of the Nineteenth Century [Do Cavalo À Eletricidade: Imaginário Ambiental E Tecnológico Na Transformação Do Sistema Ferroviário Chileno No Final Do Século Xix] [del Caballo a la Electricidad: Imaginario Ambiental y Tecnológico en la Transformación del Sistema Tranviario Chileno a Fines del Siglo Xix] - Prudant-Soto, E (Universidad de los Andes, Bogota Colombia, 2019)
Objective/Context: This article analyzes the environmental dimension of the debate that prompted the replacing of the tramway system from animal-drawn trams for electrical ones in Santiago de Chile towards the end of the nineteenth century. The objective is to delve into the correlation between the use of energy resources and urban progress through the study of the modernization of the collective locomotive system in Chile’s capital. Methodology: Based on data from newspapers, technical, business and municipal documents, it is argued that the negative consequences of horse use for inhabitants’ transportation in the city had an impact on the technological and cultural legitimacy on the exploitation of hydric resources for energy production. Originality: In a context prone to the removal of animals from the urban setting and its subsequent substitution for new means of transport, Santiago was the site of the coalescing of transnational investors in the tecno-electric industry, the circulation of medical and sanitary discourses and the spreading of a bourgeois urban imaginary. Thus, electricity would replace animal-driven means in the tramway system, which led to the re-signifying of nature’s contribution to urbanization and the industrialization of the country. Conclusions: The water ways in central Chile became the much-needed new source for locomotive energy that would change the traditional image of Santiago. This process led to its transformation into a modern and international metropolis. Even though the urban elite did favor the use of electricity for the public transport system, other actors, in contrast, voiced their dissent against the alleged contribution, and expressed fears and distrust with respect to the benefits that such technology would bring forth to the population, especially to the poorer inhabitants. © 2019, Universidad de los Andes, Bogota Colombia. All rights reserved.